A Study On The Effect Of Polymer Concentration & Surfactant On Performance And Molecular Orientation Of Nanofiltration-surfactant Membranes - S. H. Zainal; A. R. Hassan; M. H. M. Isa (World Academy of Research & Publication, 2024)
October2014, Volume 5,No.5 International Journal of Chemical and Environmental Engineering